Associations between person‐centred care and job strain, stress of conscience, and intent to leave among hospital personnel. Issue 5 (17th June 2021) - Van Diepen, Cornelia; Fors, Andreas; Ekman, Inger; Bertilsson, Monica; Hensing, Gunnel
Abstract: Aim: To determine the associations between person‐centred care (PCC) and job strain, stress of conscience and intent to leave among healthcare professionals in Swedish hospital departments. Background: Hospitals have experienced difficulty in retaining qualified healthcare personnel. Previous studies have shown that working in a person‐centred environment could offset this challenge, but research is scarce. Design: A cross‐sectional survey design using the STROBE checklist. Methods: Healthcare professionals ( n  = 94) in six hospital departments in Sweden completed a survey measuring perceived PCC, job strain, stress of conscience and intent to leave. Data were collected from April 2019 to April 2020. Bivariate analysis was used to describe the sample and correlations between the explanatory variables and perceived PCC and its subscales. Regression analyses were performed to explore the associations between perceived PCC and job strain, stress of conscience and intent to leave. Results: The organisational and environmental support subscale of perceived PCC showed significant correlations with all explanatory variables, while the extent of personalising care subscale only correlated with job strain and intent to leave. The regression analyses showed that higher perceived PCC was associated with higher job strain, less stress of conscience and less intent to leave. Conclusion: Higher perceived PCC is associated with work‐related factors in hospital departments. There is scope for further research in this area.